MENUJU SISTEM EKONOMI PANCASILA: REFORMASI ATAU REVOLUSI - Mubyarto Mubyarto (Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
.... intellectuals are at their best when distant from politics and power... only when intellectuals step back from governing institutions will they be able to speak truth to power.... Intellectuals, therefore had to conceive of themselves as cultural worker, responsible not solely for generating ideas but also for ensuring that those ideas wound up in the minds and arguments of a thoughtful audience and public. (K. Mattson, 2002: 9, 267)Universities are introduced, without the intellectual spirit. A bureaucracy is introduced without the rigid and widespread adherence to the principal of promotion by merit, efficiency, and a public service attitude. Parliamentary democracy is introduced without the spirit of fair play, honest election, and a genuine commitment to principles. The sciences are introduced without the spirit of enquiry. The incomplete nature of the modernisation process, the substance without the spirit, is the cause of prevailing backwardness of the developing societies. (Alatas, 1977: 78-79).